Schimmelpenning Syndrome: A Case Report and Literature Review - Shwu-Meei Wang; Ya-Ju Hsieh; Kuo-Ming Chang; Hsiang-Ling Tsai; Chih-Ping Chen (Elsevier, 2014)
We report a case of a male newborn with Schimmelpenning syndrome, which presented as diffuse sebaceous nevi covering the left side of the body, from the lower chin midface to the lower leg; cardiac-ocular comorbidities were also present. We present photographs of this patient's sebaceous nevi, which may assist physicians in the early diagnosis of this condition and prevent unnecessary examinations and inadequate therapies.